Features of Optimal Modeling of Tax Mechanisms in the Leveling System of Environmental and Food Security Taking into Account Inter-Industry Externalities - SHOKHNEKH, Anna V.; SKITER, Natalya N.; ROGACHEV, Aleksey F.; PLESCHENKO, Tatyana V. (Journal of Environmental Management and Tourism; Vol 8 No 1 (2017): JEMT Volume VIII Issue 1(17) Spring 2017DO - 10.14505//jemt.v8.1(17).10, 2017)
The article presents approaches to the optimal modeling of tax mechanisms in the leveling system of environmental and food security taking into account inter-industry externalities, as well as introduces the indicators of optimal modeling in the course of leveling the negative and positive significant influences on the balance of the ecosystem.